Analisis Kompetensi Lulusan Pendidikan Ekonomi Universitas Negeri Padang di Abad 21 - Rhama Fadilla Zainal; Yulhendri Yulhendri (Jurnal Salingka Nagari, 2023)
This study aims to determine the most relevant soft skills to graduates of economic education at the Padang State University in the 21st century. This type of research is a survey research using the analytical hierarchy process method. The population in this study is graduates of economic education at Padang State University with samples of lecturers, senior teachers, teachers, private employees, entrepreneurs, government and student administration staff. This study uses purposive sampling technique with consideration of expert respondents in their respective fields. The data used is the type of primary data obtained through the distribution of questionnaires. The results of this study indicate that the most relevant soft skills with economic education graduates are the first ranked communication, the second creative thinking is ranked second, the third collaboration and creative thinking is ranked fourth. While the most chosen and carried out by graduates of economic education graduates from Padang State University is the first ranked teacher, private employees are second, entrepreneurs are third and government administration staff are ranked fourth.